Urban and rural consumers: analysing their ecologically conscious consumer behavior / Wan Kalthom Yahya, Nor Hashima Hashim and Noor Dalila Musa - Yahya, Wan Kalthom; Hashim, Nor Hashima; Musa, Noor Dalila (2016)
This paper investigates the geographical differences in sustainable consumption among Malaysians by adopting the ecologically conscious consumer behaviour (ECCB) model. With a total sample of 502 responses, a survey was developed and administered. A statistical analysis was conducted using SPSS to examine the comparison between the urban and rural groups. Two independent variables were used in this study namely; Public awareness (PA) and government regulations (GR) and the results from the independent t-test show that only GR variable has a significant difference between the respondents. However, the findings from the multiple regression analysis revealed that urban and rural respondents demonstrate no significant difference in their PA, GR and ECCB. Similarly, results from multiple linear regression analysis also indicate PA and GR are significant predictors of ECCB among the urban and rural consumers. These findings are useful in assisting the Malaysian policy makers in making decisions related to environmental education, protection laws and regulations.